2009
DOI: 10.2500/ajra.2009.23.3340
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Superoxide Anion and NADPH Oxidase Isoforms 1 and 4 (NOX1 and NOX4) in Allergic Nasal Mucosa

Abstract: These results indicate that NOX1 and NOX4 may play an important role in reactive oxygen species production, contributing to the oxidative stress in allergic rhinitis and nasal polyp tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
(36 reference statements)
2
20
1
Order By: Relevance
“…In the meantime, TGF-b1 induces ROS production as part of its signal transduction pathway through the superoxide free radical-producing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase catalytic subunit NOX4 (25). Compared with the control nasal mucosa, the oxidative stress marker malondialdehyde, NOX1, and NOX4 increase, whereas the antioxidant superoxide dismutase and nitric oxide (NO) decrease in CRSwNP tissues (26). A recent GA (2) LEN network research in 19 European centers with postal questionnaires has shown that CRS is more common in smokers than in nonsmokers (OR 1.7: 95% CI 1.6-1.9), suggesting that smoking cessation may be an important therapeutic option for CRS patients (27).…”
Section: Pathways Driving Tgf-b1mentioning
confidence: 99%
“…In the meantime, TGF-b1 induces ROS production as part of its signal transduction pathway through the superoxide free radical-producing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase catalytic subunit NOX4 (25). Compared with the control nasal mucosa, the oxidative stress marker malondialdehyde, NOX1, and NOX4 increase, whereas the antioxidant superoxide dismutase and nitric oxide (NO) decrease in CRSwNP tissues (26). A recent GA (2) LEN network research in 19 European centers with postal questionnaires has shown that CRS is more common in smokers than in nonsmokers (OR 1.7: 95% CI 1.6-1.9), suggesting that smoking cessation may be an important therapeutic option for CRS patients (27).…”
Section: Pathways Driving Tgf-b1mentioning
confidence: 99%
“…diseases, other than asthma. Moon et al (16) have shown that the expression of NADPH oxidase (NOX)1 and NOX4, and superoxide anion was increased in the nasal mucosa of patients with allergic rhinitis and nasal polyps compared to healthy individuals. Profita et al (17) reported higher FE NO and IL-5 levels and lower pH in nasal and oral EBC of children with atopic dermatitis, allergic rhinitis, and asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Moon et al. (16) have shown that the expression of NADPH oxidase (NOX)1 and NOX4, and superoxide anion was increased in the nasal mucosa of patients with allergic rhinitis and nasal polyps compared to healthy individuals. Profita et al.…”
mentioning
confidence: 99%
“…These findings might suggest that IL-17A activity generates the NF-B translocation to the nucleus via MEKK1 signaling cascades, promoting an increase of NF-B at binding sites of genes involved in nasal epithelial cells activation during airway inflammation. NOX-4, localized mainly in the epithelial layer, may play an important role in reactive oxygen species production, contributing to the oxidative stress in allergic rhinitis and nasal polyp tissues [33]. NOX family is a key component of the so-called redox signaling system regulating many cellular responses by intracellular ROS content [34].…”
Section: Discussionmentioning
confidence: 99%